Journalism concepts in the Belarusian academic discourse - Fedotova, Natallia A. (Journal of the Belarusian State University. Journalism, 2023)
The article is devoted to the analysis of the priority concepts of Belarusian journalism, which define this type of activity in educational literature. The conducted research allows us to correlate the obtained results with the normative theories of journalism and to reveal the correspondence or inconsistency with the actual working conditions of the journalist.
Keywords: journalism; priorities; goals; normative theories; discourse; educational literature